Serious Games – A New Perspective on Workbased Learning. (24th August 2015) - Ahrens, Daniela
Abstract: Since the foundation of the Serious Games Initiative of David Rejeski and Ben Sawyer in 2002 games from the genre of Serious Gaming have attracted increasingly special attention. Besides, it concerns (computer) games which do not serve excluding the entertainment, but contain such compelling elements. They serve primarily the mediation of information and education. In the area of vocational education and continuing education Serious Games are suited in particular when it is a matter of providing technical and standardized or difficult and complicated learning contents. By combining playful elements and requirements of the work process Serious Games promote the learning and achievement motivation. Furthermore, the interaction with the game generates procedural knowledge. How Serious Games can be done as an innovative way for workplace learning, is illustrated in the article on the basis of the first intermediate results of an empirical project on handling of heavy goods at the port.